Intervention to Improve Mammography Screening at a Student-Run Free Clinic - Madeline A DiLorenzo; Marika L Osterbur Badhey; Lauren Roth; Wayne B Cohen-Levy; Arvind K Badhey; Juan Lin; William B Jordan; Sarah C Nosal; Amarilys Cortijo; Ellie Schoenbaum (Journal of Student-Run Clinics, 2019)
Background: Most late-stage breast cancer occurs in those who have never been screened. Uninsured women have lower screening rates than insured women. Student-run free clinics (SRFCs) caring for uninsured women can test interventions that attempt to increase screening rates.Methods: The United States Preventive Task Force guidelines were used to determine patient eligibility for screening mammography in a SRFC. Medical students began receiving education on screening mammography on May 31, 2013 while a simultaneous intervention to streamline workflow related to mammography referrals was implemented. We assessed the change in counseling and referral rates pre- and post-intervention as well as the impact of race/ethnicity, chronic disease status, and preferred language on the likelihood of getting counseled and referred for screening mammography. We also investigated the impact of the intervention on screening mammography attendance rates.Results: We collected data from the medical records of 106 women (171 patient visits) pre-intervention and 113 women (193 patient visits) post-intervention. The intervention significantly improved the rate of mammography counseling (from 54.4% to 81.9%) and mammography screening referrals (from 37.7% to 70.6%). Preferred language, race/ethnicity, and chronic disease status were not associated with counseling and referral rates. The intervention did not improve mammography attendance.Conclusions: An education and workflow intervention in a SRFC that improved counseling and referral rates did not improve mammography attendance. Further studies are needed to investigate patient-level barriers that may be affecting mammography appointment attendance.